If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8sinx + -3 = 0 Reorder the terms: -3 + 8insx = 0 Solving -3 + 8insx = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 8insx = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 8insx = 0 + 3 8insx = 0 + 3 Combine like terms: 0 + 3 = 3 8insx = 3 Divide each side by '8nsx'. i = 0.375n-1s-1x-1 Simplifying i = 0.375n-1s-1x-1
| 3x-2-2x=1+2x+8 | | (2x-5)1/2=7 | | 5(3x-2)=2(x+2) | | 2(f-4)+8-4h=-3 | | 3x^2-118x+899=0 | | y=4x(2x+3)+1 | | T-12/6=4/3 | | 11x+6=8x+9 | | X*2x+3-65=0 | | 3(3x+5)=3x-1 | | 2x^2-12x+25=y | | -8x-4x=8-1 | | X*2x+3-65=65-65 | | −19/15x≥−4 | | 12/11=6/p | | 2p^2=-21-40 | | 10/9=9/q | | y/12=6/5 | | -5(y-2y)+7=-4(2y-y)+2+8y | | a=q+(k-3)d | | x+6+3x=1+3x+1 | | 10-x-6=84 | | q=a+(k-3)d | | 6x^3-11x-10=0 | | x+x+30=250 | | 17=-5x+7 | | 3-11=13 | | 1/8-3/8 | | (f+9)(f+7)=0 | | -10x-5=5 | | 25-x-13=5 | | 2d^3-13d-7=0 |